Spatial wave structure created by wind input - Adcock, T; Taylor, P (2008)
Waves on the open sea grow under the influence of strong winds. However, most wave models used in offshore engineering neglect any energy input or dissipation. This paper explores the possible effects of energy transferred from the wind on the nonlinear dynamics of steep wave groups. Whilst for uni-directional propagation, all that occurs is the preferential amplification of solitons, in directional spread wave groups, energy input can trigger the formation of complex geometric structures in the wave field. Copyright © 2008 by The International Society of Offshore and Polar Engineers (ISOPE).